Maldivian teachers' practices of teaching thinking and their influence on students' decision making styles - Hassan, Nazira (Institute of Education, International Islamic University Malaysia, 2011)
In this information age, teaching thinking skills has become increasingly important, as young people are not competent thinkers. The purpose of this research was to determine the extent to which secondary school teachers in Maldives demonstrate thinking skills in their classroom instruction. Furthermore, this study examines the relationship between teachers' practice of teaching thinking and its influence on students' decision-making styles among selected secondary school students in the capital city Malé-Maldives. Samples of 354 students were randomly selected from eight secondary schools, in which four were public schools and four were private schools. The sample (n = 354) consisted of 177 students from public schools and 177 students from private schools. The study employed the survey method. Two instruments were used to collect data in this study. In order to find out teachers' practices of teaching thinking, a questionnaire developed by Suhaila Hussain (2000) was adopted. In order to find out students' decision-making styles, a well established Melbourne Decision-making questionnaire was used (Man et al, 1997). Analysis of the collected data led to several conclusions. The findings of this study reveal that most of the teachers often emphasize higher order thinking skills than lower order thinking skills. This study also found that teachers use teaching strategies that can enhance students' thinking. The teaching strategy teachers always use is based on Blooms Taxonomy. Findings also reveal that there is no significant difference in teachers' practices of teaching thinking with regard to grade level and type of school. Findings also showed that there is a positive relationship between teachers' practice of teaching thinking and students' decision-making style, namely vigilance and procrastination.